2019
DOI: 10.1186/s12885-019-6040-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotype affects survival in patients with hepatocellular carcinoma

Abstract: Background: There is currently no evidence that hepatitis C virus (HCV) genotype affects survival in patients with hepatocellular carcinoma (HCC). This study aimed to investigate whether the HCV genotype affected the survival rate of patients with HCV-related HCC. Methods: We performed a retrospective cohort study using the data of patients with HCV-related HCC evaluated at two centers in Korea between January 2005 and December 2016. Propensity score matching between genotype 2 patients and non-genotype 2 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Data were initially extracted from 15 selected studies[ 18 , 20 , 21 , 22 - 35 ] which provided information from a total of 12674 participants ( ). Preliminary analysis of the studies showed that these studies combined genotype data even with their primary focus on G3.…”
Section: Resultsmentioning
confidence: 99%
“…Data were initially extracted from 15 selected studies[ 18 , 20 , 21 , 22 - 35 ] which provided information from a total of 12674 participants ( ). Preliminary analysis of the studies showed that these studies combined genotype data even with their primary focus on G3.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear what causes HCV genotype 3 to behave aggressively. However, the poor prognosis associated with HCV genotype 3 infection may also be attributed to hepatic steatosis, rapid fibrosis and insulin resistance [50]. Due to the non-availability of the genotype 3 virus stock, we utilized HCV-JFH1 (genotype 2 a) as a model to validate our work in cell-culture studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] In addition, other factors associated with poor survival include alcohol consumption, age, smoking status, diabetes mellitus (DM), disease duration, viral genotype, and co-infection with other hepatotoxic viruses. [ 5 6 7 8 9 ] Moreover, CHC infection is a major cause of mortality among patients with concurrent HIV infection. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%